Perilaku Pencarian Informasi Stray Kids (K-Pop) oleh Kelompok Penggemar melalui Twitter - Fahimah, Hanifah Basirah Azizah (UI Scholars Hub, 2025)
K-pop is a type of music that is popular with the public, especially teenagers. One of the popular K-pop music groups is Stray Kids. Stray Kids has a lot of fans, which is around 4.5 million seen from Stray Kids followers on social media. Based on this, this research was conducted to analyze how fans search for the latest Stray Kids information through Twitter social media using the Wilson theory method which consists of context of information needed, activating, intervening variables, activating mechanism and information seeking behavior. Based on the research conducted, the results were found in the form of informants knowing what information they wanted to look for, namely the latest information on Stray Kids and already knowing how to obtain this information, then pressure from within themselves triggered the informant to seek this information, then the five influences of the variables explained by Wilson (2000) also influences informants in seeking information, reciprocity from fellow fans also influences informants in seeking information, as well as patterns of information behavior arising from simultaneous informants namely ongoing research where informants search for the latest Stray Kids information every day deliberately.